Surgical management of chronic genital lymphoedema. (5th July 2018) - Hennessey, Derek B; Kinnear, Ned; Chee, Justin
Abstract : A 44-year-old man with a spinal cord injury was referred to a specialist urology service with a 7-year history of significant genital swelling. His condition had eluded diagnosis and was refractory to all previous treatments. The considerable swelling both impacted his quality of life and prevented the patient from adequately managing his neurogenic bladder. He was diagnosed with chronic idiopathic genital lymphoedema and underwent total scrotectomy, wide penile skin excision and split skin graft to the penile shaft. The patient made an excellent recovery. We present this unusual case with preoperative, intraoperative and postoperative images.